Analisis Kualitas Audit Laporan Keuangan Inspektorat Daerah Kabupaten Boalemo - Fibriyanti S. Lakoro (Universitas 45 Surabaya, 2024)
The aim of the research is to determine the quality of the audit of the financial reports of the Boalemo Regency Regional Inspectorate. The research method is descriptive research with a qualitative approach. Types of research are primary data and secondary data, data collection methods are observation, interviews and documentation. The data analysis technique uses the Miles and Huberman analysis model, where activities in data analysis are through data reduction, data display and conclusions or verification. The results of the research are (1) Auditors who are competent in carrying out financial audits at the Regional Inspectorate of Boalemo Regency ideally understand government standards in the region, (2) Time pressure will not interfere with the quality of financial audits of the Regional Inspectorate of Boalemo Regency, (3) Proven work experience has an influence on the level of quality of financial analysis of the Boalemo Regency Regional Inspectorate auditor's financial analysis, (4) The Boalemo Regency Regional Inspectorate auditor's ethics in carrying out the audit includes institutional ethics, (5) The auditor's independence in carrying out the audit is carried out well but the independence of the results which includes the response to the audit results is not yet shows excellent results.